Syair Dan Realitas Sosial Bangsa Arab - Nur Hamim (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
Syair poetry is a literary product that is created using beautiful language, although sometimes it requires interpretations. Language as defined by Ibn Khaldun in his muqaddimah book, namely kala> m (words) used by a people to express its purpose. For this reason, language can be used by humans for various purposes, politics, business, education, art, and others. It can be used to express sadness, joy, fear, longing, love, and more. In the simple terms it can be said that language is a symbol of human life. For a certain society, language is very important. The occurrence of communication, diplomacy, instructions, correspondence, and others is closely related to language. For this reason, poetry in Arabic culture has become a very powerful social tool. This is in line with the view of life of the 5th century Athenians; language has become an instrument to achieve certain goals that are concrete and practical. Language is considered a powerful weapon in high-level political circles. Therefore, poetry is a popular literary work among Arabs.